Fatty Acid Content and Profile in Ulva lactuca in Response to Exposure to Variable Growth Conditions in Indoor Photobioreactors - Nabeel Gnayem; Razan Unis; Rima Gnaim; Alexander Chemodanov; Álvaro Israel; Jallal Gnaim; Alexander Golberg (Life)
Seaweed presents a sustainable alternative source of valuable fatty acids (FAs) involving omega-3 (n-3) and omega-6 (n-6). As such, there is great potential to reduce pressure on wild fish populations, helping to combat overfishing and its associated global impacts. This study explored the effect of various environmental factors on the FA content and profile of Ulva lactuca using indoor photobioreactors. The taxonomic identity of U. lactuca was confirmed through DNA sequencing using 3 markers (rbcL, ITS, and tufa). The effects of temperature (8, 20, and 30 °C), seawater salinity (3.5, 3.0, 2.5, and 2.0% w/v), nutrient type and concentration (0 or 6.4 ppm, consisting of 50% w/w N-NO3, 50% w/w N-NH4, and 0–1 ppm P-PO4), and irradiance (50, 100, and 150 μmol photons m−2 s−1) were evaluated. This study assessed their influence on U. lactuca’s biomass production rate (BPR), dry weight (DW), ash content (AC), and FA composition after 7 and 21 days. The results revealed that after 21 days, the polyunsaturated FA (PUFA) content decreased with the increasing seawater salinity (i.e., 38.9% ± 0.7, 33.8% ± 0.4, and 27.0% ± 0.4, and 6.6% ± 0.1 for a salinity of 2.0, 2.5, 3.0, and 3.5% w/v, respectively). The content of n-3 after 21 days increased significantly under the following conditions: 8 °C, a salinity of 2.5% w/v, 6.4 ppm of nitrogen without the addition of phosphorous, and an irradiation of 50 and 150 μmol photons m−2 s−1, affording a low n-6/n-3 proportion that fits a desirable level of an n6/n3 ratio (1–10) for a balanced nutritional diet.